Institutional Synergy and Maritime Domain Awareness in Indonesia: A Document-Based Analysis of BAKAMLA, KPLP, and POLAIRUD in Preventing Natural Resource Exploitation at Karimun Besar Waters - Pulungan, Ahmad Ari Syahputra; Yusnaldi; Budiman Djoko Said (International Journal of Education, Vocational and Social Science, 2025)
Indonesia’s maritime governance faces persistent challenges due to overlapping authorities and fragmented coordination among its main maritime enforcement agencies: BAKAMLA, KPLP, and POLAIRUD. This study aims to analyze the institutional synergy among these agencies in preventing the exploitation of natural resources in the strategic waters of Karimun Besar. Using a qualitative descriptive method with document analysis and triangulation, this research examines legal documents (Law No. 32/2014, Presidential Regulation No. 178/2014, Government Regulation No. 5/2020), institutional reports, and academic literature. The results show that interagency synergy remains suboptimal due to inconsistencies in legal mandates, overlapping jurisdiction, and weak technological integration for data sharing. The study proposes the establishment of a National Maritime Security Coordination Framework supported by an integrated Maritime Domain Awareness (MDA) system to strengthen surveillance and coordination. Policy recommendations include the standardization of joint patrol SOPs, the development of an interagency data-sharing platform, and the creation of a Joint Maritime Operation Center (JMOC) in strategic areas such as Karimun Besar. Strengthening institutional collaboration and data integration is essential for achieving effective maritime domain awareness and realizing Indonesia’s vision as a Global Maritime Fulcrum.